Disowning the self: The cultural value of modesty can attenuate self-positivity. Issue 6 (3rd June 2017) - Shi, Yuanyuan; Sedikides, Constantine; Cai, Huajian; Liu, Yunzhi; Yang, Ziyan
ABSTRACT: Western participants endorse a higher number of positive traits as self-descriptive, but endorse a lower number of negative traits as self-descriptive. They also respond quicker to categorize positive traits as self-descriptive, but respond slower to categorize negative traits as self-descriptive. Is this self-positivity bias qualified by the cultural value of modesty? We induced modesty (vs. punctuality) and assessed self-descriptiveness judgments and response times among Chinese participants. We replicated the self-positivity bias in regards to both self-descriptiveness judgments and response times. In the case of self-descriptiveness judgments, however, the bias was partially qualified by modesty. Relative to control participants, those in the modesty condition endorsed fewer positive traits as self-descriptive and manifested a tendency toward endorsing more negative traits as self-descriptive. In the case of response times, the self-positivity bias was unqualified by modesty. Within both conditions, participants were quicker to categorize positive traits as self-descriptive and were slower to categorize negative traits as self-descriptive. The results speak to the relation between the self-positivity bias and the self-reference effect and illustrate the malleability of self-processing.